The OPVI trial – perioperative hemodynamic optimization using the plethysmographic variability index in orthopedic surgery: study protocol for a multicenter randomized controlled trial. Issue 1 (December 2015) - Fischer, Marc-Olivier; Daccache, Georges; Lemoine, Sandrine; Tavernier, Benoît; Compère, Vincent; Hulet, Christophe; Bouchakour, Chems; Canevet, Christophe; Gérard, Jean-Louis; Guittet, Lydia; Lorne, Emmanuel; Hanouz, Jean-Luc; et al.
Abstract Background Hemodynamic optimization during surgery is of major importance to decrease postoperative morbidity and length of hospital stay. However, conventional cardiac output monitoring is rarely used at the bedside. Recently, the plethysmographic variability index (PVI) was described as a simplified alternative, using plug-and-play noninvasive technology, but its clinical utility remains to be established. Methods/design The hemodynamic optimization using the PVI (OPVI) trial is a multicenter randomized controlled two-arm trial, randomizing 440 patients at intermediate risk of postoperative complications after orthopedic surgery. Hemodynamic optimization was conducted using either the PVI (PVI group) or conventional mean arterial pressure (control group). The anesthesiologist performed the randomization the day before surgery using an interactive web response system, available 24 hours a day, 7 days a week. The randomization sequence was generated using permutated blocks and stratified by center and type of surgery (knee or hip arthoplasty). Patients and surgeons, but not anesthesiology staff, were blinded to the allocation group. The primary outcome measure is the length of hospital stay following surgery. The attending surgeon, who was blinded to group assessment, determined hospital discharge. Secondary outcome measures are theoretical length of hospital stay, determined using a dedicated discharge-from-hospital checklist, postoperative arterial lactate level in the recovery room, postoperative troponin level, presence of serious postoperative cardiac complications, and postoperative acute kidney insufficiency. Discussion The OPVI trial is the first multicenter randomized controlled study to investigate whether perioperative hemodynamic optimization using PVI during orthopedic surgery could decrease the length of hospital stay and postoperative morbidity. Trial registration ClinicalTrials.govNCT02207296 .